(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aims to explore the various purposes behind consumers’ use of social media and to analyze how these purposes differ based on individual opinions and demographic factors. Social media platforms serve multiple functions, including entertainment, communication, information gathering, brand interaction, and online shopping. However, the reasons for using these platforms can vary widely among users, influenced by factors such as age, gender, lifestyle, and personal interests. By examining different consumer perspectives, this research seeks to identify patterns in social media usage and understand how consumers perceive the value and impact of these platforms in their daily lives. The findings of this study will provide valuable insights for marketers, businesses, and content creators to develop more targeted and effective social media strategies.